1996
DOI: 10.1115/1.2831572
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Amorphous Carbon Nitride Overcoats for Magnetic Thin-Film Rigid Disks

Abstract: Amorphous carbon nitride coatings of thickness of 5 and 30 nm were deposited onto 65 and 95 mm magnetic thin-film rigid disks surfaces using single-cathode and dual-cathode magnetron sputtering systems containing nitrogen-argon plasmas. Under optimum deposition conditions, amorphous carbon nitride coatings can be synthesized on ultrasmooth thin-film disks with no significant pinholes at thickness down to 5 nm, with hardness 22–28 GPa (compared to 7–12 GPa for amorphous carbon), and r.m.s. roughness as low as 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(42 citation statements)
references
References 22 publications
0
41
0
1
Order By: Relevance
“…We showed that these CNx films achieve wear rates 3-4 times lower than those of amorphous carbon films tested under similar conditions [26], suggesting that CNx can potentially be a replacement overcoat material for next-generation computer disk surfaces. High level compressive stress may be needed to make metastable crystalline ~I-C3N4.…”
mentioning
confidence: 93%
“…We showed that these CNx films achieve wear rates 3-4 times lower than those of amorphous carbon films tested under similar conditions [26], suggesting that CNx can potentially be a replacement overcoat material for next-generation computer disk surfaces. High level compressive stress may be needed to make metastable crystalline ~I-C3N4.…”
mentioning
confidence: 93%
“…Unfortunately, high concentration of nitrogen is very difficult to achieve. However, films with small concentration of nitrogen have shown some interesting tribological properties [4,5]. Indeed, amorphous carbon nitride is presently used as a protective coating in hard disks and read heads [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These films show the highest sp3 fraction for hydrogenated films of 75%, a hardness of 60 GPa, and a mass density of 2.9 g/cm3. Hydrogen and nitrogen containing films deposited by other methods such as variations of the sputter technique and plasma enhanced CVD have a lower sp3 fraction around 20-40%, a hardness of 15-35 GPa, an elastic modulus of 100-200 GPa, a mass density of 1.7-2.3 g/cm3, and a stress of 1-3 GPa [16,18,[19][20][21]25,26].…”
Section: Properties Of Cathodic Arc Amorphous Hard Carbon In Comparismentioning
confidence: 99%